What is the true clinical relevance of Simkania negevensis and other emerging Chlamydiales members?. (May 2018) - Vouga, M.; Kebbi-Beghdadi, C.; Liénard, J.; Baskin, L.; Baud, D.; Greub, G.
Abstract: Waddlia   chondrophila and Simkania negevensis are emerging Chlamydia- related bacteria. Similar to the pathogenic organisms Chlamydia pneumoniae and Chlamydia trachomatis, these emerging bacteria are implicated in human genital infections and respiratory diseases. We used a screening strategy based on a newly developed S. negevensis –specific quantitative real-time PCR (qPCR) and a pan- Chlamydiales qPCR. We could not detect S. negevensis in 458 respiratory, genitourinary, cardiac and hepatic samples tested. One urethral swab was positive for W. chondrophila. We observed a low prevalence of Chlamydiales in respiratory samples (1/200, 0.5%), which suggests that C. pneumoniae is an uncommon respiratory pathogen. Furthermore, we screened 414 human serum samples from Switzerland, England and Israel and observed a low prevalence (<1%) of exposure to S. negevensis. Conversely, humans were commonly exposed to W. chondrophila, with seroprevalences ranging from 8.6% to 32.5%. S. negevensis is not a clinically relevant pathogen, but further research investigating the role of W. chondrophila is needed.